Data from: Widespread grounding line retreat of Totten Glacier, East Antarctica, over the 21st century - Pelle, Tyler; Morlighem, Mathieu; Seroussi, Helene; Nakayama, Yoshihiro (Dryad, 2021)
Totten Glacier, the primary ice discharger of East Antarctica, contains
3.85 m sea level rise equivalent ice mass (SLRe) and has displayed
ocean-driven dynamic change since at least the early 2000s. We project
Totten’s evolution through 2100 in a fully coupled ice-ocean model, forced
at the ocean boundaries with anomalies in CMIP6 projected temperature,
salinity, and velocity. Consistent with previous studies, the Antarctic
Slope Current continues to modulate warm water inflow towards Totten in
future simulations. Warm water (-0.5-1oC) accesses Totten’s sub-ice shelf
cavity through depressions along the eastern ice front, driving sustained
retreat of Totten’s eastern grounding zone that cannot be captured in
uncoupled models. In high emission scenarios, warm water overcomes
topographic barriers and dislodges Totten’s southern grounding zone around
2070, increasing the rate of grounded ice loss 3.5-fold (10 to 35 Gt/yr)
and resulting in a total 4.20 mm SLRe loss by 2100. In this data
publication, we present the model output and results associated with the
Geophysical Research Letter's manuscript 2021GL093213:
“Widespread grounding line retreat of Totten Glacier, East Antarctica,
over the 21st century”. We include all coupled and uncoupled ice sheet
model results and the initial-state ice sheet model. In addition, we
include the temperature, salinity and velocity mean rate-of-change fields
that were applied to the northern, eastern, and western ocean boundaries
following CMIP6 low and high emission scenarios. We also include example
ocean model output from the initial ocean model state and at 2070 for all
coupled experiments, an ocean model data file that details the setup and
grid of the ocean model, and the ocean model bathymetry and initial ice
shelf draft files. Lastly, we include the time series of the mean strength
of the Antarctic Slope Current for all couped experiments, as well as the
script used to facilitate coupling between the ice sheet and ocean model.
Please note that we do not include all ocean model output, as the number
and size of the associated files is too large; however, the data available
here is sufficient to reproduce all manuscript figures and recreate the
model-coupling.
Ice sheet model results: Direct results taken from the Ice-sheet and
Sea-level System Model (Larour et al. 2012) with no processing applied,
given bi-monthly. Ocean model results: Direct results taken from the MIT
General Circulation Model (MITgcm, Marshall and Clarke, 1997) with no
processing applied. Strength of the Antarctic Slope Current: The east-west
component of the ocean velocity (direct output of the MITgcm) was averaged
at 118oC along the continental slope at depths between 280-820 m from
January 1, 2017 to December 15, 2099 (bi-weekly). Ice shelf draft: Direct
output from BedMachine Antarctica (Morlighem et al., 2020) over ice
covered regions of the ocean model domain, no processing has been applied.
Ocean bathymetry: Bathymetry below floating ice is taken from BedMachine
Antarctica (Morlighem et al., 2020) and from ETOPO1 over open ocean
(National Geophysical Data Center), with recent updates of more accurate
bathymetry for the region on the continental shelf off Totten ice shelf
from Rintoul et al. (2016). Data was linearly interpolated between the
different data sets to allow for a smooth transition. Ocean boundary
forcing files: Monthly CMIP6 projected ocean temperature (T), salinity
(S), east-west velocity (U), and north-south velocity (V) was extracted
along the ocean model boundaries (northern, eastern, and western) between
January 2017 and December 2100 following low (SSP126) and high (SSP585)
emission scenarios from four global climate models: CNRM-CM6-1,
CNRM-ESM2-1, UKESM1-0-LL, and MIROC-ES2L. At every grid cell along a given
boundary, we compute the rate of change of a given field between 2017 and
2100, providing us with rates of change in ocean T, S, U, and V for each
global climate model. At each boundary, we then model-average of these
rate of change fields with respect to a specific variable. In the end, we
are provided with anomalies in T, S, U, and V at the eastern, western, and
northern ocean model boundaries.
Keywords: FOS: Earth and related environmental sciences